2012
DOI: 10.1093/jhered/ess073
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity-Fitness Correlations in Adult and Juvenile Zenaida Dove, Zenaida aurita

Abstract: Understanding how fitness is related to genetic variation is of crucial importance in both evolutionary ecology and conservation biology. We report a study of heterozygosity-fitness correlations in a wild, noninbred population of Zenaida Doves, Zenaida aurita, based on a sample comprising 489 individuals (382 adults and 107 juveniles) typed at 13 microsatellite loci, resulting in a data set comprising 5793 genotypes. In both adults and juveniles, and irrespective of sex, no evidence was found for an effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 86 publications
2
10
0
1
Order By: Relevance
“…We found no evidence for an influence of body size on the survival rate of male and female adults, despite the fact that we assessed the relationship from two different indexes of body size and considered both linear and quadratic effects. We are confident that this was not the result of some imprecision in body measurements as previous analyses have shown that our estimates of both wing chord and tarsus length were highly repeatable (Monceau et al 2013a). It is possible that failure to detect an effect of body size on survival could be due to the low variance in body size observed at the population level.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We found no evidence for an influence of body size on the survival rate of male and female adults, despite the fact that we assessed the relationship from two different indexes of body size and considered both linear and quadratic effects. We are confident that this was not the result of some imprecision in body measurements as previous analyses have shown that our estimates of both wing chord and tarsus length were highly repeatable (Monceau et al 2013a). It is possible that failure to detect an effect of body size on survival could be due to the low variance in body size observed at the population level.…”
Section: Discussionmentioning
confidence: 49%
“…The population is characterized by limited gene flow with, and morphological differentiation from, neighbouring populations located on other islands in the Lesser Antilles (Monceau et al 2013a). Previous analyses have shown that body size differs between territorial individuals and individuals feeding in flocks on alternative food resources (Sol et al 2005;Monceau et al 2011Monceau et al , 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…The island of Barbados was formed approximately 700,000 YBP by tectonic uplift and was then colonised by birds via natural invasion from the much older Lesser Antillean volcanic islands (Lovette et al 1999). However, a recent study (Monceau et al 2013b) found no evidence for genetic bottleneck in the Barbados population of Zenaida doves. Alternatively, inbreeding might exist at a reduced spatial scale if individuals do not disperse far away from their natal territories.…”
Section: Discussionmentioning
confidence: 90%
“…Although it is generally considered that gene flow is less restricted in populations of birds compared to other vertebrates because of their higher dispersal capacity, this is not necessary true of populations living on relatively isolated small islands. Indeed, recent analyses (Monceau et al 2013b) show very limited contemporary gene flow between Barbados and other islands in the Lesser Antilles. In addition, although sex-biased dispersal can limit inbreeding in a large number of bird species (Greenwood 1980), evidence exists for nonindependent male and female sibling dispersal in some bird species (Alberico et al 1992;Matthysen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among adult marmots, however, no correlation between MLH and fitness was revealed (Cohas et al., 2009). Recent studies have further emphasized the importance of assessing multiple age classes in the detection and direction of HFCs (Annavi et al., 2014; Brommer et al., 2015; Canal et al., 2014; Monceau, Wattier, Dechaume‐Moncharmont, Dubreuil, & Cezilly, 2013). …”
Section: Introductionmentioning
confidence: 99%